2021
DOI: 10.1186/s12917-021-02976-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age, sex, and body size on the blood biochemistry and physiological constants of dogs from 4 wk. to > 52 wk. of age

Abstract: Background Blood biochemistry and reference intervals help to differentiate between healthy and ill dogs as well as to provide information for the prognosis, evaluation, and monitoring; however, these intervals are often obtained from adult animals. It is essential to understand that puppies and adults are physiologically different, which justifies the need to obtain age-specific biochemical reference intervals. The aim of this research was to assess the potential effect of age, sex, body size,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 32 publications
1
17
1
Order By: Relevance
“…In the same study, age and gender were not reported to affect serum creatinine concentrations 37 . However, in another dog study, it was reported that while sex did not affect serum AST and ALT activities, or LDH and creatinine concentrations, age did 20 . In our study, there was no significant effect of age, sex, and age–sex interaction on serum creatinine, CK and ALT activities, or LDH, Mg, and P concentrations in serum biochemical analytes in Kangal shepherd dogs.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…In the same study, age and gender were not reported to affect serum creatinine concentrations 37 . However, in another dog study, it was reported that while sex did not affect serum AST and ALT activities, or LDH and creatinine concentrations, age did 20 . In our study, there was no significant effect of age, sex, and age–sex interaction on serum creatinine, CK and ALT activities, or LDH, Mg, and P concentrations in serum biochemical analytes in Kangal shepherd dogs.…”
Section: Discussionmentioning
confidence: 84%
“…25 In addition, it was reported in this study that bone formation and resorption decreased with age, and resorption increased in aged dogs. 20 On the other hand, in studies conducted in humans, an increase in serum OC and parathyroid hormone (PTH) concentrations and a decrease in 25 hydroxy-vitamin D were reported in geriatric females, and it was reported that this contributed to the formation of bone diseases in geriatric patients. 30 in the kidney and intestine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…None of dogs included in the study showed clinical symptoms of disease; hematological and hematochemical parameters were within the reference range for the canine species [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%